A Semantic Analysis of Michael Learns to Rock’s (MLTR) Songs - Tatik Miarsih; Hastuti Retno Kuspiyah; Yahya Yahya (Channing : Journal of English Language Education and Literature, 2018)
This study concerns with the A Semantic Analysis of Michael Learns to Rock's (MLTR) Songs. This study proposes problems are 1) what are the lexical meanings in the lyrics of Michael Learns to Rock's (MLTR) songs?, 2)What are the contextual meanings in the lyrics of Michael Learns to Rock's (MLTR)? The purpose of this study is to find out the lexical and contextual meaning that is used by Michael Learns to Rock's song lyrics. Therefore, this analysis used the descriptive method because it is to describe the lexical and contextual meaning in MLTR's song lyrics. There are five songs lyrics. Then, in this study, the procedure used in the data collection are (1) reading and comprehending the lyrics; (2) identifying the words used in the lyrics; (3) Marking and finding the meaning of the words found in the lyrics; (4) concluding the data analysis. Based on the finding, the writers found two kinds of meanings used in Michael Learns to Rock's Songs lyrics. They are lexical and contextual meaning used in the lyrics of Michael Learns to Rock's songs. They are 1) Paint My Love consists of 3 words; years, crazy and paint. 2) Sleeping Child consists of 4 words; Milky Way, paradise, cover, and hold. 3) That's Why (You go away) consists of 4 words; Left, thing, man and way. 4) Love will never Lie consists of 4 words; Run-down, road, lie and hear. 5) 25 Minutes consists of 4 words; Girl, done, hungry, and hear.